Extended Essay Of The Representation Of Legislator Candidate In Their Campaign Banner - Andrianto, Dimas Rizal (LANTERN (Journal on English Language, Culture and Literature), 2015)
Language is the prime communicative system for the human beings. But it is not the only way to communicate. Language plays an important role in creating and maintaining our interpersonal relation and the social rule that lies behind them. One of language features is that it is a tool for representing knowledge as the writer used in this research, for describing a meaning. There are three metafunctions in creating meaning: Ideational, interpersonal, and textual. The ideational metafunction is closely connected to the research. Since, this research deals with ideational meaning, the theory that will support this research is the Transitivity System by M.A.K Halliday.